Authoritarianism vs Democracy as a Key Contradiction in Approaching the Study of Political Leadership - Ilya E. Strelets (RUDN Journal of Political Science)
This study examines current trends in political leadership research in the context of theoretical and methodological debates regarding the key dichotomies of personality vs institution, authoritarianism vs democracy. In most scientific publications, especially by foreign authors, these concepts are interpreted not so much substantively as ideologically, turning into markers of commitment to conservative or liberal narratives. ‘Democratic transit’ through ‘color revolutions’ in the context of intensive information exchange intensifies the multidirectional trends of globalization and glocalization, introducing into the sphere of public policy leaders with dubious subjectivity who do not justify the hopes of either foreign beneficiaries, or local elites, or the population. Attempts to build political institutions where decisions are made not by leaders, but by elites, in countries that are not part of the circle of Western democracies, prove unviable. The purpose of this article is to separate ideological clichés from definitions, turning to the aspects of an authoritarian personality in the context of political leadership. It is concluded that the personological approach is fundamental in the study of this phenomenology, which implies consideration of a set of personal traits of a politician in the process of implementing his/her powers. This makes it possible to move away from the incorrect assessment of a leader according to the model of democrat vs autocrat towards the development of an analytically oriented method. Since at present in the West it is customary to consider ‘democracy’ the political system in those states that correspond to the WEIRD category, then the form of government in other regions can be characterized by representatives of the West as autocracy, regardless of the election system, regulations for the exercise of power, its change and other factors. This view is a relic of the unipolar world concept, demonstrating rigidity and agonism, which contradicts the concept of multipolarity, which is adhered to by Russia and its partners in various associations, including BRICS. This article contributes to the study of the multidimensional phenomenon of political leadership in terms of removing conceptual and methodological contradictions.